2009
DOI: 10.1007/s10886-009-9699-0
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Dormancy Affects the Quantity and Quality of the Female Sexual Attractiveness Pheromone in Red-sided Garter Snakes

Abstract: Low temperature dormancy is a necessary requirement of the annual cycle of most nonmigratory, temperate vertebrates. The red-sided garter snake, Thamnophis sirtalis parietalis, overwinters in communal dens during its prolonged winter dormancy (8 mo), and upon emergence, reproductive behavior of both sexes is maximal. Previous work on this species showed that male courtship behavior is maximally induced after simulated low temperature dormancy. The purpose of this study was to determine whether low temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…There is interesting variability within groups, especially among females, and this corroborates findings from other studies on the composition of the red-sided garter snake sex pheromone (e.g. LeMaster and Mason, 2002;Parker and Mason, 2009). Previous work has shown that pheromone profiles can differ in their ratios of unsaturated (U) to saturated (S) methyl ketones (U:S) and that males rely on this ratio to make mate choice decisions (LeMaster and Mason, 2002;Parker and Mason, 2009).…”
Section: 02163 P0001)supporting
confidence: 89%
See 4 more Smart Citations
“…There is interesting variability within groups, especially among females, and this corroborates findings from other studies on the composition of the red-sided garter snake sex pheromone (e.g. LeMaster and Mason, 2002;Parker and Mason, 2009). Previous work has shown that pheromone profiles can differ in their ratios of unsaturated (U) to saturated (S) methyl ketones (U:S) and that males rely on this ratio to make mate choice decisions (LeMaster and Mason, 2002;Parker and Mason, 2009).…”
Section: 02163 P0001)supporting
confidence: 89%
“…Pheromone profiles were analyzed with the Multi Response Permutation Procedure (MRPP) followed by Bray-Curtis analysis using Sorenson distance for multiple comparisons [R statistical computing software (McCune et al, 2002)]. This method for pheromone analysis was also used in previous publications (Parker and Mason, 2009;Mason and Parker, 2010). We also generated the coordinates for non-metric multidimensional scaling (NMS) plots using the vegan package in R. All graphics were produced with SigmaPlot 8.0 (SysStat Software, Inc.).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 3 more Smart Citations